Frau Ava’s Antichrist: Its Composition and Translation into Lithuanian - Burov, Aleksej; Kraužlys, Modestas (Literatūra, 2020)
The present article explores Frau Ava’s (1060–1127) apocalyptic poem Antichrist, in which, for the first time in German literature, the opponent of Christ is the protagonist. Antichrist will be Frau Ava’s second poem translated into Lithuanian. By drawing on canonic and apocryphal texts of the Scripture as well as on patristic literature, the article aims to identify traces of written and oral forms of Christian apocalyptic tradition found in the poem. The main focus will be on Adso Dervensis’ (circa 910–992) text De ortu et tempore Antichristi. The analysis of the composition of Antichrist suggests that Ava did not only translate and compile well-known narratives and motifs but also displayed a variety of artistic expressions unattested in apocalyptic tradition. Moreover, the article provides a Lithuanian translation of 118 lines of the poem.
Keywords: Frau Ava; apocalyptic; the character of Antichrist